2003
DOI: 10.1177/0013161x03253411
|View full text |Cite
|
Sign up to set email alerts
|

Educational Leadership and Student Achievement: The Elusive Search for an Association

Abstract: This study revisits the existing scholarly debate on the possible impact of the principal's leadership on student achievement. Both `direct effect' and `indirect effect' models are discussed. A quantitative meta-analysis examines to what extent principals directly affect student outcomes. The small positive effects found in this meta-analysis confirm earlier research findings on the limitations of the direct effects approach to linking leadership with student achievement. Finally, lines of future research inqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
397
2
40

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(483 citation statements)
references
References 20 publications
20
397
2
40
Order By: Relevance
“…Araştırmada, meta-analiz çalışmalarının daha bütüncül ve anlamlı sonuçlar verebileceği ifade edilmiş, üretilen doktora tezlerinin özellikle uygulamadaki sorunların çözümüne ışık tutacak ve etkin politikalar üretilmesine katkı sağlayıcı nitelikte olması gerektiği vurgulanmıştır. Witziers, Bokser ve Krüger (2003Krüger ( ), 1986Krüger ( -1996 yıları arasında farklı ülkelerde eğitimsel liderliğin, okul başarısı üzerine etkisini inceleyen çalışmalar üzerinde meta-analizi yapmıştır. Sonuç olarak, araştırmacılar, ilköğretimde görevli eğitim liderlerinin akademik başarı üzerinde etkilerinin olduğunu; ancak, ortaöğretim seviyesinde akademik başarı ve eğitim liderliği arasında böylesi bir ilişkinin görülmediğini belirtmektedirler.…”
Section: Tartişma Ve Sonuçunclassified
“…Araştırmada, meta-analiz çalışmalarının daha bütüncül ve anlamlı sonuçlar verebileceği ifade edilmiş, üretilen doktora tezlerinin özellikle uygulamadaki sorunların çözümüne ışık tutacak ve etkin politikalar üretilmesine katkı sağlayıcı nitelikte olması gerektiği vurgulanmıştır. Witziers, Bokser ve Krüger (2003Krüger ( ), 1986Krüger ( -1996 yıları arasında farklı ülkelerde eğitimsel liderliğin, okul başarısı üzerine etkisini inceleyen çalışmalar üzerinde meta-analizi yapmıştır. Sonuç olarak, araştırmacılar, ilköğretimde görevli eğitim liderlerinin akademik başarı üzerinde etkilerinin olduğunu; ancak, ortaöğretim seviyesinde akademik başarı ve eğitim liderliği arasında böylesi bir ilişkinin görülmediğini belirtmektedirler.…”
Section: Tartişma Ve Sonuçunclassified
“…The model assumes that a traditional view of the two ends of the continuum as incompatible is characteristic of a lower level of leadership development and the ability to reconcile these extremes is characteristic of a higher level of development. Witziers et al (2003) have suggested Quinn's model as an interesting approach for further research on educational leadership and its relation with context and school climate. They gave three reasons for the use of this model in future research.…”
Section: Role Conceptions and Role Priorities Leadership Behavior Amentioning
confidence: 99%
“…First, the model has been used fruitfully to distinguish different school cultures with different consequences for student outcomes (Maslowski, 2001). According to Witziers et al (2003), the framework assumes an association between particular leadership values and behaviors on the one hand and the existence of a specific school culture on the other. Second, the model focuses on the relationship between values and behaviors.…”
Section: Role Conceptions and Role Priorities Leadership Behavior Amentioning
confidence: 99%
See 2 more Smart Citations